ANTLER'S GROWTH OF THE ENDANGERED AND ENDEMIC BAWEAN DEER (Axis kuhlH Muller & Schlegel, 1842) - Gono Semiadi; Koestoto Subekti; I Ketut Sukatama; Burhanudin Masy'ud; Lukman Affandy (BRIN Publishing (Penerbit BRIN), 2003)
Bawean deer (Axis kuhlii) is an endangered Indonesian deer that is quite unique since its habitat is isolated and the species is endemic to the Bawean Island. Data on its biology is very limited. especially those related to antler's growth. Monitoring the antler's growth from the post weaning age (3-4 months) to 22 months old showed that, this process was related to the animal's reproductive physiology, starting at the age of six months, when the testes entered the scrotum. and a rapid body growth occured. At the age of 21 months, the animal had its first full hard antler's. The stag had its longest period of hard antler's at least for more than eight months. There seemed to be a close relation between the body growth cycles and theantler's growth. Hair molting lasted for 25-40 days. These results indicated that the period of physiological change in relation to antler's growth and some reproductive activities in the Bawean deer were within the cycle of other temperate and tropical deer species.